2013
DOI: 10.4161/cc.23723
|View full text |Cite
|
Sign up to set email alerts
|

Ras-induced ROS upregulation affecting cell proliferation is connected with cell type-specific alterations of HSF1/SESN3/p21Cip1/WAF1pathways

Abstract: Oncogenes of the RAS family regulate many of the cell's activities, including proliferation, survival and differentiation. Activating mutations in these genes are common events for many types of cancer. One of the contradictory points concerning the biological significance of Ras activation is its dual effect (pro- or anti-proliferative) on cell reproduction. One of mechanisms by which Ras proteins influence cell growth is a regulation of intracellular level of reactive oxygen species (ROS), second messengers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 48 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…[25][26][27] Previous study showed let-7 is complementary to multiple sequences in the 3 0 UTR of human RAS genes, and represses its expression. 28 NF-kB can act as downstream of Ras pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Previous study showed let-7 is complementary to multiple sequences in the 3 0 UTR of human RAS genes, and represses its expression. 28 NF-kB can act as downstream of Ras pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that p21 regulation is sensitive to redox status (27,28), but the underlying mechanism is not clear. Mild oxidative stimulation was shown to cause rapid nuclear export and a transient decrease in p21 protein levels (27), while p21 protein levels increased in response to sublethal doses of H 2 O 2 (29,30), inducing G2/M-phase and multi-phase cell cycle arrest in human lung cancer cells (29).…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis, total and nuclear protein extract preparation was performed as previously described. 39 Primary antibodies specific to E-cadherin (M126, Takara), vimentin (M0725, Dako), b-catenin (M3539, Dako), a-tubulin (sc-23948, Santa Cruz Biotechnology), histone H3 (9715, Cell Signaling) and Alexa488-conjugated secondary antibodies were used, band detection was performed using variable mode imager Typhoon9410 (GE Healthcare). The quantitation of protein bands was performed using TotalLab v.2.01 software.…”
Section: Reverse Transcription-pcr Assaymentioning
confidence: 99%